OPPORTUNITIES OF TRANSVAGINAL ECHOCARDIOGRAPHY FOR EARLY PRENATAL DIAGNOSIS OF INBORN HEART DISEASES IN FETUS - E.A. Shevchenko (Вопросы современной педиатрии, 2008)
According to the literature data, transvaginal echocardiography (Echocg) is the method, used for the doppler diagnostics in early terms of pregnancy (if principles of safety are observed). This method allows detecting about 70–97% of all prognostic cally significant inborn heart diseases in fetus, beginning at 12 week of pregnancy. a scheme of research includes estimation of four chamber cut of fetus heart, and study of state of its main arteries. This is an expert investigation, because it needs special grounding of specialist, high resolution ultrasonic equipment, and considerable expense of time. Wile parameters are estimated, it is necessary to use normative rates of sizes of ventricles and main arteries of fetus, developed by Russian experts, taking into account individual variations.Key words: transvaginal echocardiography, diagnosis, inborn heart disease.